2018
DOI: 10.48084/etasr.2100
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Water Filtration Units for Reduction of pH, Turbidity, Solids and Electricity Conductivity

Abstract: The main objective of this study was to analyze the performance of different filtration units that reduce turbidity, pH, total dissolved solids (TDS) and electrical conductivity (EC) of canal water. For that, three different types of filtration units, namely, slow sand, rapid sand and dual media were fabricated. Typical parameters of canal and filtered water, like pH, turbidity, TDS and EC were examined, and then the filtered water quality was compared with World Health Organizations (WHO) standards. Maximum p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…It should be noted that pH is one of the parameters which is most affected by the mixed treatment system, as it has been reduced from alkaline to almost neutral (Figure 2A). This performance can also be observed in fast, slow and mixed sand filters for obtaining drinking water (Laghari et al, 2018). In fact, this parameter has enormous importance in wastewater treatment, due to the high influence on biological, chemical or physical treatments (Aelterman et al, 2006;Issabayeva and Dih, 2019).…”
Section: Performance Of the Physicochemical Parameters In The Mixed Treatment Systemmentioning
confidence: 83%
See 1 more Smart Citation
“…It should be noted that pH is one of the parameters which is most affected by the mixed treatment system, as it has been reduced from alkaline to almost neutral (Figure 2A). This performance can also be observed in fast, slow and mixed sand filters for obtaining drinking water (Laghari et al, 2018). In fact, this parameter has enormous importance in wastewater treatment, due to the high influence on biological, chemical or physical treatments (Aelterman et al, 2006;Issabayeva and Dih, 2019).…”
Section: Performance Of the Physicochemical Parameters In The Mixed Treatment Systemmentioning
confidence: 83%
“…After applying the post-hoc test (Mann-Whitney test), it was found that point number one of the systems differs from the rest of the treatment system As for the pH, TSS, phosphates and COD parameters, those parameters have been affected by the mixed treatment system (Table 1). Both pH and TSS are significantly affected by the action of mechanical filters, due to the retention of particles larger than 0.45 μm (Laghari et al, 2018) and the effect of calcium carbonate that is usually found in the sand (Holtman et al, 2018). The significant effects on phosphates are due to the action of aquatic plants when using them as a nutrient (Delgadillo-Mirquez et al, 2016), whereas the effects on COD are mainly due to the path taken by the water through the various mechanical filters, which promotes oxygenation and thus the degradation of organic matter (Achak et al, 2019).…”
Section: Spatial Dynamics For the Mixed Treatment Systemmentioning
confidence: 99%
“…At the filtration stage for plant Z, a decrease in turbidity (89.7%) and conductivity (43.4%) was observed compared with that of raw water (Figure 2). This was ascribed to the removal of particulate matter and dissolved ions from the water to the sand bed during the contact period (Laghari et al, 2018). The 0.9% increase in the conductivity for plant S could be due to the ions from the ferric sulfate introduced at the coagulation stage.…”
Section: Resultsmentioning
confidence: 99%
“…The values of the unfiltered samples slightly decreased to 211.48 mhos/cm in the Cimahi River and 228.2 mhos/cm in the Cijenggel River. The results suggest that the EC content is slightly higher in dissolved conditions than in particulates (Laghari et al, 2018;Shrestha and Basnet, 2018). Another important thing is that the EC value in the unfiltered sample taken from the plantation-impacted watershed (Cijanggel River) was higher than that of the settlements-impacted watershed (Cimahi River).…”
Section: Water Characteristicsmentioning
confidence: 85%